The Effectiveness of the Learning Process Homeschooling as a School Alternatives in the Time of the Covid-19 Pandemic - Gusmanti, Reza; Hatimah, Ihat; Saepuddin, Asep (Universitas Negeri Padang, 2021)
This research is motivated by the outbreak of the Corona virus since May 2020 causing fear and anxiety for everyone in various aspects of life, including the world of education, students, parents and teachers are also the impact of the COVID-19 pandemic outbreak. Moreover, the massive spread of this virus has penetrated throughout the country so that it is declared a pandemic condition. One solution that is highly recommended by WHO and supported by health experts and government policies is to maintain physical social distance. These conditions have an impact on the implementation of the program at home only. This requires all activities that were originally carried out outside the home to move into the house. Of course, this adaptation change presents quite a serious polemic, especially in the process of implementing learning, the term school from home (SFH) has become a new order in the world of education. So there are various innovations in the learning process from home, so that children continue to absorb knowledge even though they do not come to school. One of the educational services that serve the implementation of learning from home, especially in conducting guidance is homeschooling. This learning implementation service through homeschooling is an alternative to implementing learning that strongly supports the absorption of knowledge for children who do not have the opportunity to attend formal schools. The method used in this research is a descriptive qualitative method. Ways to obtain data in this study include observation, interviews and documentation. Based on the results of research findings in the field, it can be concluded that the learning process through homeschooling based on learning services from home is considered effective during the Covid-19 pandemic, where parents, teachers can work together in monitoring children while studying from home more effectively on children's development in learning. study from home.